Extended exp (-? (?))-expansion method for some exact solutions of (2+1) and (3+1)-dimensional constant coefficients KdV equations - Inan, Ibrahim E.; İnç, Mustafa; Yepez-Martinez, H.; Mahmoud, K.H. (Shanghai Jiaotong University, 2022)
We gained some exact solutions of the (2+1)- and (3+1)-dimensional constant coefficients KdV equations by using extended exp(??(?))-expansion method. These solutions we gained are hyperbolic, trigonometric, exponential and rational solutions. In addition, we provided both two-dimensional and three-dimensional graphics of the solutions we found in ?10?x?10 and ?1?x?1 intervals. Then, we observed, via Mathematica 11.2, that the solutions prove the equations. This method has been used for obtaining exact travelling wave solutions of nonlinear partial differential equations (NLPDEs). © 2022
Keywords: (2+1)- and (3+1)-dimensional constant coefficients KdV-equations; Exact solutions; Extended exp(??(?))-expansion method